The farm worker and the 'drift to the land'. Roots, routes, opportunities and constraints to career pathways in farming. (April 2021) - Nye, Caroline
Abstract: The mass decline in agricultural labour in Britain since the industrial revolution has, until recently, led to the farm worker being fundamentally overlooked within the agricultural research agenda over the last fifty years, while labour shortages in farming persist at a global scale. Data regarding those who actively work at the 'frontline' of agriculture is minimal, as are understandings of the career pathways linked to non-capital related occupational succession in agricultural occupations. Using empirical evidence from a survey of 1251 farms in the South West of England, as well as 45 semi-structured interviews with farmers, farm workers and agricultural contractors, this study employs the Human Capability Framework to examine the career trajectory of the farm labour contributor, and identifies potential constraints to a sustained career in agriculture. Findings demonstrate that farm labour contributors largely, but not always, stem from an agricultural background, arriving via one of three pathways; direct, further/higher education or post-travel, and that farm-level, local-level and national-level constraints exist which influence the capacities and opportunities available to a potential farm worker. Such constraints ultimately affect the ability not only to recruit staff and contend with labour shortage issues in the sector, but also to match employees' and employers' suitably to one another. Highlights: The majority of farm workers in the study came from a farming background. Several routes are taken to a career in farming. Farm-level, local-level and national-level constraints exist which impede the career pathway.